INTERCULTURAL EDUCATION TECHNOLOGY OF STUDENTS IN EXTRACURRICULAR WORK BY MEANS OF MUSIC - Zheyuan, Wei (The Modern Higher Education Review, 2017)
In the article the intercultural education technology of students in extracurricular work by means of music is highlighted; the essence and basic features of music and educational technology; examples of educational music-teaching technologies are provided; the stages of implementation of educational technology are described. The author analyses the basic principles of intercultural education content selection of means music students in extracurricular work formulated and substantiated the content of education students, which includes two parts: theoretical and practical. The content of the theoretical unit aimed at fostering cultural values and tolerance towards university students to general and music culture of Western Europe (Germany, Austria, Italy, France) and Far East (Mongolia, China, Korea, Japan) based on mastering their theoretical knowledge and skills to identify specific ethnic and typological features music culture of these countries; musical styles and genres, and features of folk and spiritual music, classics, works by contemporary composers each country. A practical content unit of intercultural education of students by means of music in classroom work aimed at fostering intercultural communication skills, identifying specific in the musical culture of different nations, tolerance towards musical culture of other countries during the learning of theoretical material.